Regulation Of Cybersecurity Technology As An Effort To Address Security Threats To Privacy In The Digital Era - Agustinus Wempy; Zaenal Efendi; Marsudi Dedi Putra (Fakultas Hukum Dehasen, 2024)
Cybersecurity technology regulations play a key role in ensuring adequate protection of individual data privacy in an increasingly complex digital era. In the context of the collection, use, and dissemination of personal data by various entities, these regulations provide a foundation for governing practices related to data privacy. Through regulations such as the General Data Protection Regulation (GDPR) in the European Union, stringent standards are enforced to protect personal data and grant individuals control over their data. Transparency, restrictions on data use and access, and the implementation of robust data security measures are key aspects of this regulation. Additionally, law enforcement and sanctions for data privacy violations are integral parts of effective cybersecurity regulations. Thus, cybersecurity technology regulations aim to create a safe and trustworthy digital environment where individual data privacy is respected and optimally protected.